Determinants and pregnancy outcomes of maternal glycemia - Yong, Heng Yaw (2017)
Both gestational diabetes mellitus (GDM) and hyperglycemia less severe than GDM are commonly associated with risk of adverse pregnancy outcomes. This study consisted of two phases. The first phase of study was to determine the cut-off point for maternal hyperglycemia for the detection of adverse pregnancy outcomes. The second phase of study was to determine the factors and outcomes of pregnancies complicated by maternal hyperglycemia. The first phase of study was a retrospective cohort study involving 1,356 pregnant women who were registered with and attended antenatal checkups at two Maternal and Child Health (MCH) clinics in Seremban District, Negeri Sembilan. The antenatal booklet kept at the MCH clinic was used as a data source. Demographic and socioeconomic, obstetrical, anthropometric, biochemical and birth information of infants were extracted. Hyperglycemia was defined as either or both fasting plasma glucose (FPG) 4.8–5.5 mmol/l or two-hour plasma glucose (2hPG) 7.5–7.7 mmol/l. GDM was diagnosed according to the Ministry of Health’s (MOH) criteria of either or both FPG ≥ 5.6mmol/l or 2hPG ≥ 7.8 mmol/l.The second phase of study was a prospective cohort study in which a total of 282 pregnant women with normal glycemia were recruited from three MCH clinics in Seremban District, Negeri Sembilan and followed-up until delivery. A standard 75g Oral Glucose Tolerance Test was performed between 24–32ndweeks of gestation. Socio-demographic, anthropometric, biochemical, dietary, physical activity, smoking, and other data were collected using a pre-tested, interviewer-administered questionnaire at follow-ups of women. Pregnancy and birth information were obtained from medical records. A majority of the pregnant women were Malays (85.1%) in the age range of 18-43 years. According to pre-pregnancy Body Mass Index, 11.0%, 20.2% and 13.5% of them were underweight, overweight, and obese, respectively. About 30.1% of the women had at risk waist circumference (≥ 80cm). Meanwhile, the mean rate of weight gain was 0.38 kg/week for the second and third trimesters. Mean fasting plasma glucose (FPG) and two-hour plasma glucose (2hrPG) were 4.35 ± 0.47 mmol/l and 5.99 ± 1.56 mmol/l, respectively. About 10.6% and 8.9% of the women were hyperglycemic, less severe than GDM and GDM, respectively. The mean energy intake of the pregnant women was 2,135 ± 686.26 kcal/day. The mean percentage of energy contributed by macronutrients was 51% by carbohydrate, 17% by protein and 32% by fat. While the mean intake of folate (47.09 ± 28.49% RNI) was below the recommended level, the mean intake of iron (108.18 ± 71.86% RNI) and calcium (116.52 ± 81.93% RNI) were slightly higher than the RNI recommendation. The mean for all food groups, except for grains and cereals, meat, poultry, and fish were less than the recommended servings. Three major dietary patterns were identified, namely “sweet and fatty food pattern”, “healthy pattern” and “common food pattern”. Most women consumed dietary supplements (82.6%) and did not consume alcohol (99.0%). None of them smoked. The mean daily total physical activity was 1005 minutes with a large majority of their time spent in household/caregiving activities (625 minutes/day). It may be concluded that Malaysian pregnant women are generally sedentary in their day-to-day activities, with only a small percentage being involved in sport activities or exercises. One-fifth of infants (19.9%) were born via caesarean deliveries. The mean infant’s length, head circumference and birth weight were 49.30 ± 2.58cm, 32.19 ± 1.44cm, and 3.03 ± 0.44kg respectively. More than half (56.4%) were born with a birth weight of 3.0–4.0 kg, while 9.2% were born weighing less than 2.5kg. For the birth weight percentile, 34% of infants were small-for-gestational-age (SGA), while only 10 infants (3.5%) were large-for-gestational-age (LGA). Women with an excessive rate of gestational weight gain (GWG) at second trimester showed a higher risk of hyperglycemia. In terms of dietary intake, pregnant women with higher fat intake and high common food dietary pattern were 4 and 6 times more likely to be at risk of hyperglycemia. Only a high common food pattern was found to be significantly associated with the risk of GDM. For the pregnancy outcomes, caesarean delivery was the only one to be significantly associated with GDM. The cut-off points for both FPG (4.8 mmol/l) and 2hPG (7.5 mmol/l) to detect adverse pregnancy outcomes were lower than the recommended criteria of MOH for diagnosis of GDM. Further well-designed clinical trials are needed to determine the cost-effectiveness of therapeutic strategies for management of hyperglycemia, less severe than GDM diagnosed by the present study on improving the adverse pregnancy outcomes. The rising prevalence of GDM in Malaysia and its adverse consequences underscore the need to identify the determinants for formulation of effective public health strategies. Gestational weight gain and dietary intake should be the focus of the strategies as these lifestyle factors are linked to maternal hyperglycemia.